Analyzing Inter-Leukocyte Communication and Migration In Vitro: Neutrophils Play an Essential Role in Monocyte Activation During Swarming - Walters, Nicole; Zhang, Jingjing; Rima, Xilal Y.; Nguyen, Luong T. H.; Germain, Ronald N.; Lämmermann, Tim; Reátegui, Eduardo (Frontiers in Immunology, 2021)
Neutrophils are known to be the first responders to infection or injury. However, as inflammation progresses, other leukocytes become increasingly important in inflammation propagation, tissue reconstruction, and inflammation resolution. In recent years, there has been an increase in publications that analyze neutrophil behavior in vitro, but there remains a gap in the literature for in vitro technologies that enable quantitatively measuring interactions between different types of human leukocytes. Here, we used an in vitro platform that mimics inflammation by inducing neutrophil swarming to analyze the behavior of various leukocytes in a swarming setting. Using human peripheral blood leukocytes isolated directly from whole blood, we found that myeloid cells and lymphoid cells had different migratory behaviors. Myeloid cells, which are predominately neutrophils, exhibited swarming behavior. This behavior was not seen with lymphoid cells. We perturbed the peripheral blood leukocyte system by adding exogenous leukotriene B4 (LTB4) to the medium. Notably, only the myeloid cell compartment was significantly changed by the addition of LTB4. Additionally, LTB4 had no significant impact on myeloid cell migration during the recruitment phase of swarming. To further investigate the myeloid cell compartment, we isolated neutrophils and monocytes to analyze their interaction on the platform. We found that neutrophils increase monocyte migration toward the bioparticle clusters, as measured through speed, chemotactic index, track straightness, and swarm size. These results were confirmed with in vivo mouse experiments, where monocyte accumulation only occurred when neutrophils were present. Additionally, we found that both neutrophils and monocytes release the monocyte chemoattractant proteins CCL2 and CCL3 in the presence of S. aureus bioparticles. Furthermore, extracellular vesicles from swarming neutrophils caused monocyte activation. These findings suggest that neutrophils play an essential role in the onset of inflammation not only by sealing off the site of infection or injury, but also by recruiting additional leukocytes to the site.